Supply Chain Analysis Of Beef In Kupang City - Ronald P.C. Fanggidae; Paulina Y. Amtiran; Yury S. Fa’ah; Klaasvakumok J. Kamuri; Dominikus K.T. Aman (Eduvest - Journal of Universal Studies, 2023)
The agricultural sector is one sector that plays a role in economic development in Indonesia. One of the sub-sectors in agriculture is the livestock sub-sector where the activities are in the form of livestock commodity management. In fulfilling consumer demand, the form of regulation in the meat supply chain also aims to benefit the links involved. Therefore, there is a need for approach to the supply chain system in the form of an approach to find out the product flow, financial flow, information flow, because this will affect the decision making of the existing chain. The snowball sampling technique was used for sampling the links involved in the beef supply chain in Kupang City. The method used in this research is to use the survey method. The survey phase was carried out to collect primary and secondary data. Primary data was obtained through interviews and filling out questionnaires by respondents. Secondary data was obtained from the relevant agencies in this study, namely the Kupang City RPH and other related sources. There are 3 results in this study, including 1) Product Flow Based.2) Financial Flow based on 3) Information Flow.